PERGESERAN PARADIGMA TAFSIR ALA LINGUIS (Studi atas Kitab “Qira’ah Mu’ashirah” Karya Muhammad Syahrur) - John Supriyanto (Jurnal Studi Agama, 2018)
This article attempts to explore one perspective of the knowledge of the Qur'an and interpretation. Muhammad Shahrur ad-Dayyub, a linguist with civil engineering background, offers a new approach to understanding the Qur'an. Syahrur's concept about Qur'an which published in "Al-Kitab wa al-Qur'an: Qira'ah Mu’ashirah" has been offered as the most ideal contemporary reading method in accordance with the present social dynamics. In this case, Shahrur wanted the Qur'an to be placed in a position as if it had just been revealed. The offer has been deconstructed as well as the scientific reconstruction of the Qur'an and interpretations that have been "considered" to be accepted. Some view Syahur concept as novelty that needs to be positively appreciated in the creative discourse of reading religious texts. But not a few also respond to his thoughts with criticism and even blasphemy.